(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article presents facts and opinions about STEAM technology, when and in which countries it was first used as an approach, and today it is used in the education system of the whole world, and about the effectiveness of teaching in the integrated state of several subjects. It has been revealed how relevant it is to learn the terms of integrated subjects in English at the same time that elementary school students learn the STEAM approach. The introduction of STEAM education based on international experiences changes the approach to the education system and the attitude to education today. By focusing on practical skills, future teachers will develop their knowledge of scientific research, creativity, and collaborative competencies. In today’s era of development in all areas, the reduction of educational and professional subjects without the concept of STEAM (Science, Technology, Engineering, Arts, Mathematics) and a new approach to the training of specialists cannot be realized without clear technological, engineering science and mathematics.